(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
In his famous speech against Athenenogenes Hypereides counters the argument, which the former takes from the general statute on homologein, by means of a counterargument derived from the special statute on homologein. This statute required all contents of contractual agreements to be fair. The contents of the agreement in that case were, however, unfair. For the buyer lacked the knowledge of the size of his commitment. According to Theophrastos, this knowledge is, however, necessary to achieve any fair result, corresponding to the balance of advantage an disadvantage required by Aristotelian corrective justice.